Lateral Seismic Fragility Assessment of Cable-Stayed Bridge with Diamond-Shaped Concrete Pylons - Chao Zhang; Jianbin Lu; Zhengan Zhou; Xueyuan Yan; Li Xu; Jinjun Lin (Shock and Vibration)
The cable-stayed bridge with diamond-shaped pylons is one of the most popular bridges because of its obvious advantages such as aesthetical appearance and smaller foundation. However, the diamond-shaped pylons have both inward and outward inclinations, which may result in complicated seismic behavior when subjected to lateral earthquake excitations. To end this, the finite element model of a cable-stayed bridge with diamond concrete pylon is developed firstly. Four limit states and corresponding damage index are defined for each critical section. Finally, the lateral seismic fragility of the components and system of CSB was carried out. Based on the result of probabilistic estimation of lateral seismic responses, the order of the damage probability in all four damage states for each component of bridge is given. The fragility curves of bridge system on the lower bound and upper bound are studied. Moreover, the system fragility of the entire bridge is compared with that of each component.